The Problems of Human Embryos Genome Editing from the Position of Islam Denominations - Minchenko, Tatiana; Gribkov, Edward (Conatus - Journal of Philosophy, 2024)
Biomedical technology is one of the most relevant and rapidly developing branches of science. In response to the major problems of bioethics and bio-law, bioethical dilemmas emerge in society, which constrain the abuse of new technologies. Medical discoveries, on the one hand, can greatly facilitate the life of humankind, but, on the other hand, the problem of interference in human nature actualizes the most fundamental questions concerning its ontology, the boundaries of permissible transformations, the responsibility of a scientist and a specialist, applying the latest technologies, for remote and unpredictable consequences, due to the integrity and interconnectedness of various aspects of human nature. This paper presents the experience of generalizing the attitude of the main Islamic confessions and different approaches in the legislation of Islamic countries to the problem of editing the human embryo genome. Based on a review of scientific and religious literature, it is concluded that, although the Islamic world is increasingly using Western models of behavior, in matters of the permissibility of editing the human embryo genome from the point of view of Islamic bioethics, it is necessary to rely on the principles of Sharia and multidisciplinary knowledge.